Spirulina sebagai Pengganti Artemia untuk Meningkatkan Produksi Larva Ikan Patin Pangasius hypophthalmus - Dian Eka Ramadhani; Cecilia Eny Indriastuti; Muhammad Agung Zaim Adzkiya; Andri Hendriana; Imza Hermawan (Jurnal Ilmu Pertanian Indonesia, 2024)
The provision of quality and sufficient shrimp fry for production is largely determined by the management of maintenance during larval stadia. This study aims to obtain the best treatment of natural feed in the form of Spirulina sp. and Artemia sp. as feed supplements to improve the growth performance and survival rate of patin fish larvae. The experiment used a Complete Randomized Design consisting of 4 feed treatments and 3 replicates: A (Artemia sp. 100%), B (Artemia sp. 100% and Spirulina sp. 100%), C (Artemia sp. 50% and Spirulina sp. 50%), and D (Spirulina sp. 100%). The larvae with a density of 50 heads/L were kept in the aquarium and fed according to the treatment. The density of Spirulina sp. administered was 104–105 cells/mL maintained until day 7 according to the treatment. The parameters measured included growth performance, which included specific growth rate (SGR), survival (SR), absolute length growth (PPM), and analysis of larval digestive enzymes (amylase, lipase, and protease). The data were analyzed using one way-analysis of variance and continued with Duncan's Multiple Range Test with a 95% confidence interval using SPSS version 22.0. The results showed that the administration of Spirulina sp. produced better SGR, SR, PPM, amylase enzyme, lipase, and protease activities compared to the control (100% administration of Artemia sp.). The best treatment was given by 100% Spirulina sp. treatment. Keywords: Artemia sp., digestive enzymes, patin fish larvae, Spirulina sp.